Gambaran Kejadian Anemia pada Pasien Penyakit Ginjal Kronik (PGK) di RSUD Karawang Tahun 2024 - Cahya, Karwili Dwi; Sihombing, Martina Rentauli; Pita Sari, Dominica; Timan, Ina Susianti (Universitas Kristen Krida Wacana, 2025)
Chronic Kidney Disease (CKD) is a progressive and irreversible condition characterized by a decline in the glomerular filtration rate (GFR). One of the most common complications in CKD patients is anemia. Anemia is a condition in which the number of red blood cells or hemoglobin levels in the blood are below normal. The primary cause of anemia in CKD patients is the decreased production of erythropoietin (EPO), a hormone that stimulates red blood cell formation in the bone marrow. This study aims to describe the condition of anemia in CKD patients at RSUD Karawang from January to December 2024. This is a descriptive study with a retrospective approach and a cross-sectional design. Medical record data of patients were used as the research instrument. A total of 106 samples were taken. The results showed that 57 samples were male (53.8%), and the largest age group was 41–59 years (40.6%). Out of 106 samples, 85 samples (80.2%) had anemia, with 41 samples (38.7%) presenting severe anemia. Hypertension was the most common comorbidity in CKD patients, found in 53.8% of cases.